(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Science, technology, engineering, and mathematics (known as STEM) field and related jobs are increasingly demanding, so teachers must be equipped with STEM-based knowledge during classroom instruction in preparing students with STEM-relevant skills. However, past studies showed that many teachers were less confident in applying the knowledge that practically affected students’ interest in STEM opportunities. In this study, researchers intend to measure the validity and reliability of the STEM pedagogical content knowledge instrument (STEMPCK Scale) using the Rasch model analysis. The online survey was distributed to 23 mathematics secondary school teachers’ participation. The data was analyzed using Winsteps version 3.71.0.1 software. The finding showed that all the items are valid, reliable, and compatible to measure STEM-based knowledge among school teachers. The implications of the research are discussed